2016
DOI: 10.1002/1873-3468.12293
|View full text |Cite
|
Sign up to set email alerts
|

Fungal lytic polysaccharide monooxygenases bind starch and β‐cyclodextrin similarly to amylolytic hydrolases

Abstract: Edited by Judit Ov adiStarch-binding modules of family 20 (CBM20) are present in 60% of lytic polysaccharide monooxygenases (LPMOs) catalyzing the oxidative breakdown of starch, which highlights functional importance in LPMO activity. The substrate-binding properties of starch-active LMPOs, however, are currently unexplored. Affinities and binding-thermodynamics of two recombinant fungal LPMOs toward starch and b-cyclodextrin were shown to be similar to fungal CBM20s. Amplex Red assays showed ascorbate and Cu-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…Overall, it can be concluded that as originally observed for SBDs from the family CBM20 from various amylolytic GH families and recently confirmed also for this SBD present in non‐amylolytic starch‐degrading lytic polysaccharide monooxygenases, taxonomy seems to be more respected in the evolution of CBMs than the specificity of the enzyme to which a given CBM sequence is attached.…”
Section: Resultssupporting
confidence: 79%
“…Overall, it can be concluded that as originally observed for SBDs from the family CBM20 from various amylolytic GH families and recently confirmed also for this SBD present in non‐amylolytic starch‐degrading lytic polysaccharide monooxygenases, taxonomy seems to be more respected in the evolution of CBMs than the specificity of the enzyme to which a given CBM sequence is attached.…”
Section: Resultssupporting
confidence: 79%
“…Because different structural analysis tools give different results in H-bond determination, a range in the number of H-bonds formed between the AA13 PMO and each substrate is reported, representing the H-bonds identified using a variety of analyses. A random amylose coil forms 16 -19 H-bonds with 11 residues of AA13 PMOs (Cys 25 , Ile 27 , Glu 29 , Arg 44 , Ala 52 , Arg 53 , Asn 88 , Asp 90 , Pro 172 , Lys 173 , and Gln 219 ) (Fig. S6).…”
Section: Starch Pmo Substrate Selectivitymentioning
confidence: 99%
“…These values are similar to those obtained experimentally for CBM20 complexes with b-cyclodextrin and some oligosaccharide. 18,45 For all three substrates, the binding affinity at BdS1 is signicantly larger (by 1.8-3.5 kcal mol À1 ) than that at BdS2. The average binding affinity of both binding sites deduced for ADH10, ASH10, and ASC10 is À10.9 AE 0.5, À10.2 AE 0.3, and À5.6 AE 0.3 kcal mol À1 .…”
Section: Resultsmentioning
confidence: 88%
“…4,6 Several isothermal calorimetry studies revealed 5-8 kcal mol À1 binding affinities for oligosaccharides of the CBM20s of the glucoamylase from Aspergillus niger 45 and starchactive polysaccharide monooxygenases (AA13) from Magnaporthe oryzae and Aspergillus terreus. 18 Moderate affinity for starch granules were also demonstrated for these CBM20s. Given the moderate affinity of CBM20 for starch, we have been able to use CBM20 as an affinity tag for facile purication of NCU08746, an AA13 polysaccharide monooxygenase from Neurospora crassa (NcAA13), using an amylose resin column.…”
Section: Molecular Dynamics Of the Cbm20-a3l Complexmentioning
confidence: 92%
See 1 more Smart Citation